Molecular characterization and pathogenicity of Streptococcus agalactiae serotype Ia ST7 and III ST283 isolated from cultured red hybrid tilapia in Peninsular Malaysia - Roslan, Syuhada (2019)
Aquaculture is one of the major contributor of economic resources and food production in Malaysia and tilapia (Oreochromis spp.) was one of the highest value in import and export market. But the production was reported to decrease from 51, 554 MT to 35, 996 MT from 2012 to 2016 respectively due to streptococcosis. Streptococcosis was caused by Streptococcus sp. which is the etiological agent of diseases in human and animals which could lead to different pathological effects. It was suggested that the different pathological effects post infection was caused by genetically distinction of the bacterial strain. Thus, this study was conducted to determine the molecular serotyping, virulence genes profiling and pathogenicity of Streptococcus agalactiae isolated from cultured red hybrid tilapia in Malaysia. A total of 256 isolates of S. agalactiae, isolated from fish in Peninsular Malaysia. Genotype of the bacterial collections was determined using PCR based on the capsular polysaccharide gene clusters and multilocus sequence typing. Subsequently, two serotypes were identified, which were 11% and 89% for serotype Ia ST7 and III ST283, respectively. The profiles of virulence genes were constructed using m-PCR with different types of the various published primers involving 14 standard virulence genes (fbsA, fbsB, pavA, scpB, lmb, cylE, cfb, spb1, hylB, rib, bca, bac, cspA and pbp1A/ponA). Serotype Ia showed different pattern of virulence genes profile compared to serotype III, where it lacked the lmb, scpB, pavA, fbsB, cyl, bca, cspA and bac genes, thats differentiated the virulence level of the serotype. Median lethal dose 50 (LD50) of S. agalactiae in red hybrid tilapia for serotypes Ia and III were calculated at 8.7 x 103 CFU/mL and 6.3 x 103 CFU/mL, respectively. There was no significant difference (p > 0.05) between the rate of mortality of red hybrid tilapia for both serotypes following intraperitoneal challenge. Histopathological lesions included meningitis, necrosis of hepatocytes, coagulative tubular necrosis and hypocellular of spleen. Histopathological scoring and independent t-test showed that there was the significant difference (p < 0.05) between all lesions in brain, liver (except hepatonecrotic), and spleen but not in kidney. Streptococcus agalactiae serotype Ia ST7 showed severe lesions in all organs compared to S. agalactiae serotype III ST283. This study concluded that there were two serotypes (Ia and III) of S.agalactiae isolated from cultured red hybrid tilapia in Malaysia so far. Moreover, different serotypes of S. agalactiae consisted of different virulent characteristics. Red hybrid tilapia was susceptible to both serotypes following intraperitoneal challenge. Serotype Ia showed higher LD50 compared to serotype III, but not significant (p > 0.05) in term of cumulative mortality.